Prevalence and risk factors of soil-transmitted helminthiasis among school children living in an agricultural area of North Sumatera, Indonesia - Ayodhia Pitaloka Pasaribu; Anggraini Alam; Krisnarta Sembiring; Syahril Pasaribu; Djatnika Setiabudi (BMC, 2019)
Abstract Background Soil-transmitted helminth infection (STH) is one of the neglected tropical disease that affects approximately 2 billion people globally. School children represent the age group that is most commonly infected with STHs, resulting in poor school performance, impaired cognitive function, and many other detrimental effects. The transmission of STH is determined by many factors, such as hygiene and sanitation. Understanding the factors that influence disease transmission in a particular area is key to effective STH control. The objective of this study was to determine the prevalence of STH in North Sumatera and to identify the associated risk factors among school children. Methods A cross-sectional study was carried out among primary school children in Suka village, Tigapanah subdistrict. Stool samples were processed using a single Kato-Katz method. The potential risk factors analyzed were parent education and occupation, hand washing habits, latrine usage, footwear usage and contact with soil. The Chi-square test was performed to identify an association between risk factors and parasitological results. Logistic regression analysis was used to measure the strength of association. Results We enrolled 468 school children between 6 and 12 years of age. Among those children, 268 children (57.24%) were positive for one or more STH infections. Approximately 62.39% of children played with soil/dirt every day, and only 50% regularly washed their hands after activities. Most of the children wore shoes/slippers when going outside (87.82%) and used a latrine for defecation (85.04%). Playing with soil/dirt have been shown to increase the risk of STH infections 7.53 times, while hand washing habits and latrine usage decreased the risk of STH infections 0.16 times each. Conclusion The prevalence of STH infection in school children in Suka village, Tigapanah subdistrict is still high. Playing with soil/dirt increased the risk of infection, while hand washing habits and latrine usage decreased the risk of infection. The combined strategies of improving the personal hygiene of children and biannual deworming can reduce the risk of STH infection in school children in Suka village, Tigapanah subdistrict.